Understanding PD-L1 Testing in Breast Cancer: A Practical Approach - Erber, Ramona; Hartmann, Arndt (Breast Care, 2020)
Background: Immune checkpoint inhibitors (ICI) have changed therapy strategies for cancer patients tremendously. Some approved ICI acquire testing of PD-L1 expression on tumor and/or immune cells. However, since PD-L1 testing is a comprehensive issue with various assays, antibody clones, scoring methods, and cut-offs, we aimed to summarize the recommendations and technical and histopathological issues of diagnostic PD-L1 assessment with an emphasis on invasive breast cancer (IBC). Summary: Besides other (pre)analytical considerations, selecting the most adequate PD-L1 immunohistochemical assay/antibody clone is important. In-house assay validation, prediagnostic training, and internal and external quality assurance should be implemented. The current most relevant PD-L1 assays and scores will be explained in this review. Moreover, recommendations for PD-L1 testing in IBC are outlined. Key Messages: Atezolizumab plus nab-paclitaxel therapy is approved for adult patients with locally advanced or metastatic triple negative breast cancer (mTNBC), if the tumor-Associated immune cells express PD-L1.-This PD-L1 immune cell positivity is defined as an immune cell (IC) score, which refers to the area occupied by PD-L1 positive immune cells (lymphocytes, dendritic cells, macrophages, and granulocytes) as a percentage of the whole tumor area. The cut-off is an IC score ≥1%. In the approval study for atezolizumab in mTNBC, IC score was assessed using the Ventana PD-L1 SP142 assay. Other assays or laboratory developed tests may be used depending on country-specific drug approvals. However, harmonization studies have to show whether other PD-L1 tests are reliable and of clinical value to predict the response of breast cancer patients to ICI.
CRIS-Team Scopus Importer:2020-10-30